Analysis of Lecturer and Student Perspectives on ChatGPT Utilization for Completing Assignments in Business Education (Lembaga Pengembangan Kinerja Dosen, 2025)
Chat Generative Pretrained Transformer (ChatGPT) has rapidly gained popularity and is increasingly utilized across various fields, including education, where it plays a significant role as a supporting tool for academic tasks. In the educational context, ChatGPT can assist students in preparing and completing a wide range of assignments, providing quick access to structured information and alternative perspectives. This study was designed to explore the views of both students and lecturers on the integration of ChatGPT in academic activities, specifically as a support system for handling student assignments. Employing a descriptive qualitative approach, data were collected through interviews with 5 students and 6 lecturers from the Business Education Study Program at the State University of Surabaya. The findings reveal contrasting yet complementary perspectives. From the students’ point of view, ChatGPT offers considerable benefits, particularly in enhancing independence, efficiency, and time management when working on lecture assignments. However, these advantages are accompanied by drawbacks, such as decreased creativity, reduced critical thinking, and diminished interest in consulting traditional learning resources like books. On the other hand, lecturers acknowledge the usefulness of ChatGPT in simplifying student work and accelerating the completion of assignments but express concerns regarding the overreliance on artificial intelligence, which could potentially hinder the development of essential academic skills. Overall, the research suggests that while ChatGPT presents valuable opportunities to enhance learning processes, it must be applied thoughtfully, with careful guidance from educators to balance efficiency with the cultivation of creativity, critical thinking, and academic integrity.